Application of palliative care in pain management of terminally ill patients (安宁疗护在临终患者疼痛管理中的应用) - CHEN Mingming (陈明明); REN Li (任丽); JIN Qi (金琦) (中西医结合护理)
Objective To investigate the effect of palliative care in pain management of terminally ill patients. Methods A total of 50 terminally ill patients with pain were divided into the control group and observation group according to the admission sequence, with 25 cases in each group. Patients in the control group received routine nursing and pain management, and those in the observation group were given palliative care interventions in addition. The degree of pain was evaluated using a Visual Analogue Scale(VAS). Results The VAS score was decreased in both two groups after intervention, and VAS score in the observation group was lower than that in the control group (P＜0. 01). Conclusion Palliative care is effective to reduce the pain of terminally ill patients, and it helps to improve the quality of life in terminal stage. (目的 探讨安宁疗护在临终患者疼痛管理中的应用。方法 选取医院老年科2021年1月—2022年12月收治的50例临终患者为研究对象, 均伴有不同程度的疼痛。根据入院时间将患者分为观察组和对照组, 各25例。对照组采用常规护理和疼痛管理, 观察组在对照组基础上增加安宁疗护, 对比两组患者疼痛视觉模拟量表(VAS)评分。结果 干预后两组VAS量表评分降低, 且观察组VAS量表评分低于对照组, 差异有统计学意义(P＜0. 01)。结论 安宁疗护能有效缓解临终患者疼痛, 有助于改善生存质量。)